BRS 404 - wheat cultivar for rainfed conditions - Silva,Márcio Só e (2016)
Abstract BRS 404 is a new wheat cultivar developed by Embrapa, indicated for rainfed conditions. It has a particularly good performance under heat and drought conditions. The grain yield is stable and BRS 404 is classified as bread wheat.